DEVELOPMENT OF PRIVATE LAW IN UNITED STATES – SHORT OVERVIEW OF INHERITANCE LAW (IUS LAW Journal, 2025)
With the arrival of English traders and the formation of colonies on the territory of North America, it developed the need to establish a legal system. Inheritance law, along with all other branches of private law, was present in a similar form as in England. Over time, the law changed and moved away from its English predecessor. At the beginning of the nineteenth century, each state began the process of codifying inheritance law, which differed from state to state. The twentieth century marked a turning point in the adoption of a large number of laws that regulated every area of inheritance and property management. A Unified Probate Code was created in 1969, which was fully or partially adopted by more than a third of the states. In this paper, short overview of development of the inheritance law is provided. Beginning with the colonial period, the explanation of development of forms and practices of inheritance law and probate procedures is presented. In addition, this paper deals with the period of the American Revolution, the nineteenth, twentieth and twenty-first century in the same way. Many scientific methods were used in this paper and their detailed explanation will be shown in introduction.
Keywords: Inheritance law; inheritance law in United States; development of private law; probate law